Interstitial Stereotactic Laser Anterior Corpus Callosotomy: A Report of 2 Cases with Operative Technique and Effectiveness. Issue 3 (5th July 2018) - Tao, James X; Issa, Naoum P; Wu, Shasha; Rose, Sandra; Collins, John; Warnke, Peter C
Abstract: BACKGROUND AND IMPORTANCE: Corpus callosotomy is an effective palliative treatment for medically intractable Lennox–Gastaut syndrome (LGS) that disrupts the interhemispheric synchronization of epileptiform discharges. However, traditional open corpus callosotomy carries a significant risk of surgical complications associated with craniotomy and a parafalcine approach to the corpus callosum. Here, we report 2 cases of anterior corpus callosotomy using MRI-guided stereotactic laser interstitial thermal therapy (LITT) as a minimally invasive technique for mitigating the risks of craniotomy while achieving favorable outcomes. CLINICAL PRESENTATION: Two patients with medically intractable LGS underwent stereotactic laser anterior corpus callosotomy using a 2 laser-fiber approach. Ablation of 70%-80% of the corpus callosum was confirmed by postoperative MRI diffusion tensor imaging and volumetric analysis. Marked reduction of epileptiform activity was observed in both patients during postoperative video-EEG studies as compared to preoperative video-EEG studies. Freedom from disabling seizures including drop attacks was achieved in 1 patient for 18 mo, and more than a 90% reduction of disabling seizures was achieved in the other patient for 7 mo with cognitive improvement and without surgical complications. CONCLUSION: These early data demonstrate the technical feasibility, safety, and favorable outcomes of MRI-guided stereotactic laser anterior corpus callosotomy in patients with LGS, making it a potentially safe and effective alternative to traditional open corpus callosotomy and other stereotactic methods including radiofrequency ablation and radiosurgery due to the ability to monitor the ablation in real time with MRI.